Reflexões sobre a política linguística nos PALOP (Países de Língua Oficial Portuguesa) - Vilela, Mário (Africana Studia, 2020)
The starting point for any reilection on linguistic policy in Africa is the fact that ali lhe colonial powers, wilhout exception, cndeavoured to creale favourable conditions for implementing and expanding lheir respective languages and, further, thal lhey had practically no interest in the national languages. Given lhe variety of languages existent in the lerritories designated collectively as PALOP (Países de Língua Oficial Portuguesa - Portuguese-speaking African Countries), the issue raised is that of discovering the defining traits for "national language" in lhis contexl: number of speakers or the extension of territory covered? The "language" factor is determining every plan of education in the PALOP: there are internal pressures resulting form their status as multilingual countries, and externa! pressures, resulting from the fact thal olher officiallanguages reside right next door. Plurilinguism is generalised: bilinguism or multilinguism are widespread. There are efforts to standardise lhe languages (and their varianls) and to establish some solutions, conjugating monolingual basic education (as was the case when Portugal controlled education), or bilingual education according to age groups and functions. The whole problem revolves in turn of monolinguism and bilinguism: a large part of education takes place in Portuguese (Portuguese with marked traces of the tropics) and considering that Portuguese is to ali inlents and purposes a foreign language, bilinguism is lhe norm in manuais and programmes. The dosage of this bilinguism is the major issue lo be resolved.